PKM Bimbingan Belajar Siswa SD Negeri 057239 Sekoci Langkat Sumatera Utara di Masa Pandemi Covid-19 - A Mahendra; Elseriani Nainggolan; Tiurmaduma Situmorang; Putri Sri Yosepha Br Sinaga (Prima Abdika : Jurnal Pengabdian Masyarakat, 2021)
The program to help students learn is a community service carried out at SD Negeri 057239 Sekoci, Besitang District, which is located at Sukaramai Hamlet, Sekoci Village, Langkat Regency, North Sumatra. for 1 month starting from March 31, 2021 to May 6, 2021. The activities carried out in this service are teaching and learning activities at home and helping students in doing school assignments which are carried out for 1 month. The material comes from thematic books and guidebooks from schools. In the implementation of this Community Service there are several obstacles such as: The distance to teaching at home between classes 3,4 and 5 is very far in insufficient time, Lack of attention from students in learning at home, students' awareness of their responsibility in doing assignments is still lacking, lack of communication and parental attention to their children.